Diversity, equity & inclusion at the workplace mohammad imrozuddin - Mohammad Imrozuddin (Journal of Management and Science, 2021)
Identifying how a diverse, equitable and inclusive workforce can aid in achieving business objectives aligned with the company’s strategy is the next step in the process. The organization must set specific goals related to DE&I based on the company’s strategic objectives. For example, the U.S. Department of Veterans Affairs (VA) had a goal as part of their 2014-2020 overall strategic plan to "Make VA a Place People Want to Serve."1 As part of this goal, increasing diversity index scores is one of the agency’s performance indicators. Because its clients are becoming more diverse, the agency is responding by embracing a more diverse and inclusive workforce to better serve the population. Specific diversity goals were created to recruit more white and Hispanic males as well as Hispanic females after a comparison with the available labor market.Another example might be around a business goal to create more innovative products an employer can introduce quickly to surpass the competition. To do so, the employer wishes to increase innovation in the research and development (R&D) teams. One way to accomplish this goal could be to build cultural competence and inclusive decision-making within the team through training, which could more effectively harness existing team diversity and capitalize on diverse ideas.